Effects of Five Serial Apnoeas Prior to a Running Time Trial in Competitive Athletes - Matthew John Barlow; Catherine Ross; Remmie Cockrell; Morgan Rubie; Harry Cahill; Craig Robertson; Jamie French; Antonis Elia (Journal of Science in Sport and Exercise, 2025)
Purpose This study aimed to determine whether a series of repeated maximal voluntary apnoeas is effective in improving subsequent time trial performance in competitive level track and field athletes. Methods Seventeen competitive runners volunteered for this study and based on their preferred competitive distance they were placed either in the 200 m (5 male, 4 female) or 1000 m group (3 male, 5 female). On two separate occasions (≤ 7 days apart), the participants performed a running time-trial that was preceded either by: (i) a standardised warm up (WO) or (ii) a standardised warm up succeeded by five repeated maximal dry static apnoeas (WA). Splenic volume, haematology and cardiovascular parameters were monitor at rest, before and after each time-trial. Results WA resulted in a significantly faster performance (27.51 ± 3.49 s; P = 0.009) compared with WO (27.96 ± 3.34 s) in the 200 m group, whereas no differences were observed in the 1000 m group (WA, 211.10 ± 26.18 s; WO, 215.82 ± 25.13 s, P = 0.120). No differences were noted in splenic volume between WO and WA in either group ( P ≥ 0.081). Haemoglobin was significantly elevated after breath-holding in the 200 m (+ 7 g/dL, P = 0.041) but not 1000 m group. Conclusion This study demonstrates that five repeated maximal apnoeas are capable of significantly improving a 200 m but not a 1000 m time-trial performance in competitive track and field athletes.